Association Between Device-Measured Physical Activity and Incident Heart Failure: A Prospective Cohort Study of 94 739 UK Biobank Participants. Issue 12 (29th August 2022) - Ho, Frederick K.; Zhou, Ziyi; Petermann-Rocha, Fanny; Para-Soto, Solange; Boonpor, Jirapitcha; Welsh, Paul; Gill, Jason M.R.; Gray, Stuart R.; Sattar, Naveed; Pell, Jill P.; Celis-Morales, Carlos
Abstract : Background: Studies of objectively measured physical activity (PA) have investigated acute cardiovascular outcomes but not heart failure (HF), an emerging chronic condition. This study aimed to investigate the dose-response relationship between device-measured PA and HF by intensity of PA. Methods: This was a prospective cohort study of 94 739 UK Biobank participants who had device-measured PA in 2013 to 2015 and were free from myocardial infarction and HF. PA was measured with a wrist-worn accelerometer, and time spent on light-, moderate-, and vigorous-intensity PA was extracted. Incident HF was ascertained from linked hospital and death records. Cox proportional hazard models with cubic penalized splines were used to study the associations, which were adjusted for sociodemographic and lifestyle factors. Competing risk was handled with cause-specific hazard ratios. Results: The overall incidence of HF was 98.5 per 10 000 person-years over a median 6.1 years of follow-up. Compared with participants who undertook no moderate- to vigorous-intensity PA, those who performed 150 to 300 min/wk of moderate-intensity PA (hazard ratio, 0.37 [95% CI, 0.34–0.41]) and 75 to 150 min/wk of vigorous-intensity PA (hazard ratio, 0.34 [95% CI, 0.25–0.46]) were at lower HF risk. The association between vigorous-intensity PA and HF was reverse-J shaped with a potentially lower risk reduction above 150 min/wk. Conclusions: Device-measured PA, especially moderate-intensity PA, was associated with a lower risk of HF. Current vigorous-intensity PA recommendations should be encouraged but not increased. In contrast, increasing moderate-intensity PA may be beneficial even among those meeting current recommendations.